RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KINERJA PEGAWAI PT IMPERIAL CLUB GOLF MENGGUNAKAN METODE TOPSIS - taufiq, Rohmat; Mulyati, Sri; Rohmiana, Miftahul (Jurnal Teknik, 2024)
Employee performance selection is one of the crucial aspects in human resource management that affects the success and efficiency of the organization. This selection discusses the application of the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method in selecting employee performance as an effective and transparent decision-making tool. The purpose of writing this thesis is to simplify the employee performance assessment process and provide transparent data in the employee performance assessment process at Imperial Golf Club Karawaci Tangerang. Where currently the calculation of employee performance assessments is carried out with the help of the Microsoft Excel application. The data collection method used by the author consists of observation method, interview method, and literature method. For the system analysis method, the author uses the SWOT analysis method and for the system development method, the author uses the SDLC method with the Waterfall model. As a result of this study, the author made an application of the Employee Performance Selection Decision Support System at PT Imperial Golf Club using the TOPSIS method. It is hoped that through the design of the menu of the decision support system with this topsis method, it can manage employee performance data well.Â Â